The Effects of Two Forms of Ice on Microbiological and Physiochemical Properties of Barramundi (Lates calcarifer, Bloch) Fillets - Zakhariya, S.; Fotedar, Ravi; Prangnell, D. (Wiley-Blackwell Publishing, Inc., 2015)
Barramundi (Lates calcarifer) fillets were subjected to two different ice forms (prefreezing treatments: slurry ice [SI] and flake ice [FI]) for 0 (before freezing) and 1h and 1, 2, 4, 8 and 16 days prior to blast freezing at -80C for 8 h. Fillets were then stored in a freezer at -20C for 20 days.Microbiological and physiochemical analysis were then carried out. Fillets that were exposed to pre-freezing treatments in FI demonstrated larger increase in total volatile base nitrogen, total viable count and pH; larger decrease in protein content; and smaller increase in moisture content compared with SI at the end of the frozen storage. Fillets exposed to pre-freezing treatments in FI are significantly (P < 0.05) lighter (L*), more red (a*) and more yellow (b*) than those in SI. All textural parameters fell significantly as storage time progressed in both FI and SI, with hardness falling to a greater extent in FI than SI.